Neuroprotective effects of astaxanthin in a scopolamine-induced rat model of Alzheimer’s disease through antioxidant/anti-inflammatory pathways and opioid/benzodiazepine receptors: attenuation of Nrf2, NF-κB, and interconnected pathways - Rastinpour, Zeinab; Fakhri, Sajad; Abbaszadeh, Fatemeh; Ranjbari, Mohammad; Kiani, Amir; Namiq Amin, Mohammed; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundGiven the complexity of pathological mechanisms behind Alzheimer’s disease (AD), there is a pressing need for novel multi-targeting therapeutic agents. Astaxanthin, a natural compound with diverse biological effects, has emerged as a potential candidate in neuronal diseases.PurposeThis study aimed to evaluate the neuroprotective effects of astaxanthin in a scopolamine-induced rat model of AD.Materials and methodsIn total, 36 male Wistar rats were divided into six groups, including a control group receiving normal saline, a negative control group treated with scopolamine (1 mg/kg), and two groups receiving astaxanthin at doses of 5 and 10 mg/kg. Additionally, two groups were pre-treated with naloxone (0.1 mg/kg) or flumazenil (0.5 mg/kg) to block opioid and benzodiazepine receptors, respectively, followed by receiving the most effective dose of astaxanthin (i.e., 10 mg/kg). Treatments were administered via intraperitoneal injection for 14 consecutive days and behavioral tests were done. Biochemical analyses, zymography, Western blotting, and histopathological examinations were also performed.Results and discussionAstaxanthin treatment significantly improved cognitive function, enhanced plasma antioxidant capacity by increasing catalase and glutathione levels, and reduced nitrite levels. It also increased serum activity of matrix metalloproteinase 2 (MMP-2), while decreasing MMP-9, increasing the expression of nuclear factor erythroid 2–related factor 2 (Nrf-2) and decreasing nuclear factor kappa B (NF-κB) in hippocampal tissue. Histopathological findings indicated reduced hippocampal damage after astaxanthin administration. The aforementioned protective effects of astaxanthin were reversed by naloxone and flumazenil.ConclusionAstaxanthin demonstrates protective effects against scopolamine-induced AD through its neuroprotective, antioxidant, and anti-inflammatory properties, potentially involving interactions with opioid and benzodiazepine receptors.